Legal reglementations in the European Union and Romania regarding collection management, recovery and recycle of the waste packaging - Alin-Angelin Iorga; Felix Dimitrie Ciocan; Anda Irina Angelescu; Ştefania Mihaela Lospa (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
Once with the Romania's adherence to the European Union, assuming some obligations and initiatives were imposed, from a national level to a local and a county level. Adherency to the European Union, made Romania assume its politics regarding the environment field and elaborate several plans of European directives implementations. All this plans lead to staging the directions which the European Union imposed by establishing the implementation method, delegating the component authorities and sanctioning all the implicated members, whom do not obey the environment legislation. Throughout these implementation plans, Romania requested transition and derogation periods, establishing clear terms of the implementation of all imposed requirements. Thereby, the next implementation plans were proposed: Implementation of Council Regulation (EEC) No 259/93 on the supervision and control of shipments of waste within, into and out of the European Community, Directive 2004/12/EC amending Directive 94/62/EC on packaging and packaging waste, Council Directive 1999/31/EC on the landfill of waste, Directive 2000/76/EC of the European Parliament and of the Council on the incineration of waste.
Keywords: 330; environment legislation; shipments of waste; European directives; implementation plan